[STIX]x1D711-CONTRACTIBILITY AND [STIX]x1D711-CONNES AMENABILITY COINCIDE WITH SOME OLDER NOTIONS. Issue 2 (30th January 2018) - MAHMOODI, AMIN
Abstract : It is shown that various definitions of [STIX]x1D711 -Connes amenability and [STIX]x1D711 -contractibility are equivalent to older and simpler concepts.